Power and energy analysis for a commercial retail refrigeration system responding to a static demand side response. (May 2020) - Albayati, Ibrahim M.; Postnikov, Andrey; Pearson, Simon; Bickerton, Ronald; Zolotas, Argyrios; Bingham, Chris
Highlights: A simultaneous DSR event for the refrigeration systems in three retail stores. DSR event of the store trials facilitates energy savings and the planned load shed. The aggregated loads facilitate 97.3% and 27% of load shed at start and during DSR. The synchronised return to operation post DSR drops the line voltage by 1%. A pressure offset at the beginning of a DSR improves the performance of the system. Abstract: The paper considers the impact of Demand Side Response events on the supply power profile and energy efficiency of widely distributed aggregated loads applied across commercial refrigeration systems. Responses to secondary grid frequency static DSR events are investigated. Experimental trials are conducted on a system of refrigerators representing a small retail store, and subsequently on the refrigerators of an operational superstore in the UK. Energy consumption and energy savings during 3 h of operation pre- and post-secondary DSR, are discussed. In addition, a simultaneous secondary DSR event is realised across three operational retail stores located in different geographical regions of the UK. A Simulink model for a 3Φ power network is used to investigate the impact of a synchronised return to normal operation of the aggregated refrigeration systems post DSR on the local power network. Results show ∼1% drop in line voltage due to the synchronised return to operation. Analysis of energy consumption shows that DSR events can facilitate energy savings of between 3.8% and 9.3% compared to normal operation. This is a result of the refrigerators operating more efficiently during and shortly after the DSR. The use of aggregated refrigeration loads can contribute to the necessary load-shed by 97.3% at the beginning of DSR and 27% during the 30 minutes of a DSR, based on results from a simultaneous DSR event carried out on three retail stores.